A política urbana na legislação federal face ao conceito de justiça social territorial - OLIVEIRA, Everson Carlos Nascimento (Universidade Federal do Pará, 2017)
This paper makes an analysis on the compatibility of the general guidelines of the Brazilian urban policy, expressed in the Law 10.257 / 01 - Statute of the City, with the territorial social justice theory of David Harvey, making it an essentially theoretical work. The reasons to seek verify the compatibility of the law with Harvey's theory stem from the fact that the Statute has in several articles, among its objectives is to promote social justice in the cities. To carry out his profession, the work is structured as follows. In Section 1 the introduction is made. In it the research objectives are presented, the methodology used and the main authors discussed, as well as the structure of the text. In section 2 is made a discussion on the urban space, their way of production and use of its soil. Section 3 is made a discussion of territorial social justice and national urban policy, especially focusing on the principles of social function of the city and the social function of property, as well as analysis of some legal instruments established by law 10.257/01 e that help check the compatibility. Finally, in section 4 are made the final considerations.